Development of a learning model for writing scientific articles based on blended learning integrated creative problem solving - Oktavia, Yunisa; Atmazaki; Zaim, M. (Universitas Muhammadiyah Malang, 2023)
Learning to write scientific articles necessitates the development of creative ideas and concepts in order to produce high-quality work that is also novel. However, learning to write scientific articles has become uninteresting among students due to a lack of interest in reading, ineffective use of digital literacy services to obtain references, and difficulties in creatively expressing ideas in scientific writing. The research goal is to create a learning model for writing scientific articles based on blended learning and creative problem solving. The Plomp model is used in the research method, which has three stages: preliminary, prototype, and assessment. The research yielded a trilogy of models: model books, lecturer books, and student books. The trilogy of models is designed based on the results of needs and context analysis, analysis of learning model characteristics to write scientific articles in universities, and prototypes by designing model books, lecturer books, student books, and assessments. The assessment results show that: (a) the model book is 89,44%, the lecturer's book is 94,44%, and the student book is 91,67% very valid. (b) A practicality test revealed that 85% of model books, 85,71% of lecturer books, and 87,27% of student books were very practical. (c) The practical 87,602% very effective. The characteristics of the blended learning integrated creative problem-solving learning model for writing scientific articles are very interesting and creative when combined with two lecture methods between online and offline (hybrid) using blended learning to improve students' creative thinking skills. The learning process incorporates technology and blended learning components to help students understand and gain new experiences in creative writing of scientific papers.